2005
DOI: 10.1139/b04-151
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of mycorrhizal fungi isolated from neotropical orchids in Brazil

Abstract: To initiate a conservation program of the Orchidaceae from the Brazilian Atlantic rain forest with the purpose of ex situ conservation or reintroduction in the State of Minas Gerais, seven mycorrhizal Rhizoctonia-like fungal strains were isolated from roots of seven neotropical orchid species from three different Atlantic rain forest fragments. Taxonomic studies revealed that the isolates belong to the genera Ceratorhiza and Epulorhiza. The Epulorhiza isolates were identified as Epulorhiza repens (N. Bernard) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 45 publications
2
37
1
17
Order By: Relevance
“…1; Pereira et al 2009). Outros trabalhos buscaram isolar fungos presentes em protocormos e plântulas coletadas no campo ou a partir de protocormos obtidos após incubação de sementes das orquídeas de interesse no seu habitat natural (McKendrick et al 2002;Pereira et al 2005a).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…1; Pereira et al 2009). Outros trabalhos buscaram isolar fungos presentes em protocormos e plântulas coletadas no campo ou a partir de protocormos obtidos após incubação de sementes das orquídeas de interesse no seu habitat natural (McKendrick et al 2002;Pereira et al 2005a).…”
Section: Discussionunclassified
“…A maioria dos fungos micorrízicos isolados de orquídeas é identifi cada como fungos semelhantes à Rhizoctonia ou rizoctonióides, sendo os principais gêneros Rhizoctonia, Ceratorhiza e Epulorhiza (Pereira et al 2005a;b;Dearnaley 2007). Estes fungos estão dispersos nos ambientes naturais, exercendo outros papéis ecológicos como saprófi tas, pató-genos ou simbiontes de espécies vegetais de outras famílias (Rasmussen 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The degree to which tropical orchids utilize fungi is unclear, but we have attempted to understand the orchidmycorrhizal association in our studies by isolating and identifying fungal symbionts (Pereira et al 2003b;2005b;Valadares et al 2015), by germinating seeds of tropical orchids (Pereira et al 2005a;2011;Guimarães et al 2013) and by characterizing protocorm development. Histological studies have also contributed to understanding the mechanisms involved in the mycorrhizal association (Arditti 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have researched tropical orchids in South and Central America (Otero et al 2002;2004;Pereira et al 2005;Otero et al 2007;Otero & Bayman 2009;Pereira et al 2009;Valadares et al 2012;Oliveira et al 2014;Pereira et al 2014), but only one demonstrated ITS rDNA sequences from mycorrhizal fungi in Colombia (Mosquera et al 2010;. In Ecuador, Suarez et al (2006) isolated mycorrhizal fungi belonging to the genera Tulasnella and Sebacina.…”
Section: Introductionmentioning
confidence: 99%